Entrepreneurial strategic content - Lumpkin, G. T.; Katz, Jerome A. (Emerald, 2009)
The theme of this volume is Entrepreneurial Strategic Content. As such, it addresses the types of strategies that entrepreneurial companies use to effectively position themselves and gain competitive advantages. As a companion to Volume 10 (Entrepreneurial Strategic Processes), Volume 11 identifies several strategic dilemmas and strategic choices that organizations face in their efforts to be more entrepreneurial. Top researchers from a diverse set of perspectives - including Saras Sarasvathy, Per Davidsson, Tom Dean, and Kaye Schoonhoven - have contributed their latest research on a variety of topics such as celebrity entrepreneurship, innovation in traditionally conservative settings (banking and the military) and acquisitions as an entrepreneurial growth strategy. The strategic implications of tax policy and the importance of knowledge management and human resources management to the success of entrepreneurial strategies are also highlighted. The last two chapters constitute a spirited debate between researchers with sharply different views about the role of individual versus collective effort to entrepreneurial progress and success. Volume 11 identifies important strategic alternatives that entrepreneurial companies use to optimize performance and provides valuable insights into how organizations of all types use entrepreneurial strategies to achieve competitive advantages.
Keywords: Entrepreneurship.; elektronické knihy; electronic books